PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN INKUIRI PADA MATERI BARISAN DAN DERET UNTUK KELAS XI SMA/MA - Nur Aziela; Elfis Suanto; Sehatta Saragih (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Learning in schools must be well planned, one of which is to create learning tools that refer to the 2013 curriculum. This research produces learning tools (syllabus, Learning Implementation Plan, and Student Worksheets) using the inquiry model in the progression and series material. This research is a research and development (R&D) using the 4-D model. The research instrument was an instrument of validity in the form of a validation sheet to assess the feasibility of the syllabus, RPP and LKPD and practical instruments in the form of a teacher's questionnaire response to the Syllabus, RPP and LKPD, a questionnaire for students' responses to LKPD, and an observation sheet on the implementation of learning.Validation data analysis results obtained an average value for the syllabus is 3.53 in the category of very valid which means that the syllabus is feasible to use; and the average value for the RPP is 3.61 and LKPD is 3.53 in the very valid category which means that the RPP and LKPD are worth testing. The results of practicality data analysis in small group trials were 3.61; Large group trials found that the teacher response questionnaire was 3.79; student response questionnaire was 3.62; and the implementation of the learning process is 3.76 in the very practical category which means that the Syllabus, RPP and LKPD are appropriate to be used in schools.Key Words: Mathematics Learning Tools, Inquiry Model, Development Research, 4-D Development Model